1981
DOI: 10.1161/01.atv.1.2.144
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ethanol-induced modifications in hyperlipoproteinemia and atherosclerosis in nonhuman primates (Macaca nemestrina).

Abstract: Male Macaca nemestrina were studied In an experiment with a 2 X 2 factorial design. Diets contained low vs high cholesterol levels (0.3 vs 1.0 mg/Kcal) and no ethanol or ethanol, as 36% of the calories substituted isocalorically for carbohydrate. After receiving their diets for 18 months, the monkeys had blood samples drawn for lipoproteln analyses, and then were killed for evaluation of the extent of atherosclerosis. Ethanolfed groups had significantly Increased concentrations of serum cholesterol, triglyceri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

1983
1983
2008
2008

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(17 citation statements)
references
References 17 publications
(7 reference statements)
0
16
1
Order By: Relevance
“…Therefore, the differences observed in the rate of accumulation of cholesterol in the perfusates are primarily due to differences in the hepatic secretion rate of cholesteryl esters (Table III). The increase in size of plasma LDL in cholesterolfed monkeys has been shown to be primarily due to an increased number of cholesteryl oleate and cholesteryl palmitate molecules per LDL particle (2,41). Thus, the cholesteryl esters that increase in number in large molecular weight LDL are more likely to have been formed by acyl-CoA cholesteryl O-acyltransferase than by LCAT (42,43 The only form of apo B that was detected on the perfusate lipoproteins including the VLDL was the large molecular weight form, apo Bloo, termed apo B-1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the differences observed in the rate of accumulation of cholesterol in the perfusates are primarily due to differences in the hepatic secretion rate of cholesteryl esters (Table III). The increase in size of plasma LDL in cholesterolfed monkeys has been shown to be primarily due to an increased number of cholesteryl oleate and cholesteryl palmitate molecules per LDL particle (2,41). Thus, the cholesteryl esters that increase in number in large molecular weight LDL are more likely to have been formed by acyl-CoA cholesteryl O-acyltransferase than by LCAT (42,43 The only form of apo B that was detected on the perfusate lipoproteins including the VLDL was the large molecular weight form, apo Bloo, termed apo B-1 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The hypercholesterolemia that develops when nonhuman primates are fed a high-fat, high-cholesterol diet is consistently characterized by an increase in the molecular weight of plasma low density lipoprotein (LDL) (1,2). The increase in LDL molecular weight has been found to be highly correlated with the severity of coronary artery atherosclerosis (2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence in nonhuman primate models has been obtained over the past two decades indicating that the accumulation of cholesteryl esters in low density lipoprotein, with the associated low density lipoprotein particle enlargement, is highly correlated with the extent of coronary artery atherosclerosis (35)(36)(37)(38). Most recently, we have shown that the secretion of cholesteryl esters from the liver, as monitored during isolated liver perfusion, is correlated with the enrichment of the low density lipoprotein particles with cholesteryl esters and is also predictive of the extent of coronary artery atherosclerosis (12).…”
Section: Discussionmentioning
confidence: 99%
“…'- 3 LDL particle size has been highly correlated with the extent and severity of coronary artery atherosclerosis (CAA). 3 -5 Increased LDL size is characterized by an increase in the number of cholesteryl ester molecules in the core of the particle, with smaller increases in the surface constituents of LDL.…”
mentioning
confidence: 99%